Inflation-free Pricing Rules for a Generalized Commodity-Reserve Currency - Luke, Jon C. (Journal of Political Economy, 1975)
Let currency be issued with several commodities as backing. If certain pricing rules are strictly followed, it is shown that currency can then be redeemed without restriction for any of the commodities and that, according to a certain definition, the currency retains constant value, so that general inflation cannot occur.